Shared decision making in high-grade glioma patients—a systematic review. Issue 6 (24th July 2020) - Sorensen von Essen, Helle; Piil, Karin; Dahl Steffensen, Karina; Rom Poulsen, Frantz
Abstract: Background: Shared decision making (SDM) has proven to be a valuable approach in different patient populations when treatment decisions are called for. Along the disease trajectory of high-grade glioma (HGG), patients are presented with a series of treatment decisions. At the same time, HGG patients often experience cognitive deterioration and reduced decision-making capacity. This study aimed to review the current knowledge about shared decision making from the perspective of the HGG patient. Methods: Systematic searches were performed in MEDLINE, CINAHL, PsycINFO, and EMBASE. Studies were reviewed against the inclusion criteria and assessed for methodological quality. Descriptive data from the included studies were extracted and a narrative synthesis of the findings was performed. Results: The searches resulted in 5051 original records. Four studies involving 178 HGG patients fulfilled the inclusion criteria. The narrative synthesis revealed that most HGG patients in the included studies appreciated an SDM approach and that sufficient information and involvement increased patients' emotional well-being. The use of a patient decision aid showed the potential to increase knowledge, decrease uncertainty, and affect the treatment decision making of HGG patients. Conclusion: The results indicate that many HGG patients prefer an SDM approach and that SDM can lead patients toward improved emotional well-being. The evidence is weak, however, and firm conclusions and practice guidelines concerning SDM in HGG patients cannot be made. Future research is warranted to improve decision support for HGG patients.